Validation of CFD model of multiphase flow through pipeline and annular geometries. (18th August 2019) - Sultan, Rasel A.; Rahman, M. Aziz; Rushd, Sayeed; Zendehboudi, Sohrab; Kelessidis, Vassilios C.
ABSTRACT: Accuracy of prediction of pressure losses plays a vital role in the design of multiphase flow systems. The present study focused on the development of a computational fluid dynamics model to predict these parameters conveniently and accurately. The main objective was to validate the developed model through comparison of its simulation results with existing experimental data and empirical correlations. Both pipeline and annular geometries were considered for validation. Several data sets that involved a significant variation in process conditions were used for the validation. All three phases—liquid (water), gas (air), and solid (sand)—were taken into account. The simulations were conducted using the workbench platform of ANSYS Fluent 16.2. The Eulerian model of multiphase flow and the Reynolds stress model of turbulence closure available in Fluent were used for the present study. The average velocities and volumetric concentrations of involved phases were specified as the inlet boundary conditions. The stationary surfaces of the flow channels were hydrodynamically considered as either smooth or rough walls, and the outlets were regarded as being open to the atmosphere. The simulation results of pressure loss showed a good agreement with the corresponding measured values as well as with the predictions of well-established correlations.